Pengaruh Lama Penyimpanan Terhadap Kadar Air Dan Jumlah Mikrobia Pada Mi Basah Dari Komposit Tepung Ubi Jalar Ungu Dan Tepung Tapioka - Shiddiiqah, Aisyah; , Pramudya Kurnia, STP, M.Agr; , Eni Purwani, S.Si., M.Si (2017)
Purple sweet potato flour has the characteristics of amylose and amylopectin which is almost like wheat flour so it can be processed into a wet noodle. Tapioca flour can be used as an adhesive in wet noodle dough from purple sweet potato flour so that the dough does not fragile. The purpose of this research was to determine the effect of storage time on the water content and the number of microbes in a wet noodle composite flour. This type of research was experimental with a completely randomized design. Variations in storage time were 0 hours, 12 hours, 24 hours and 36 hours. The water content was tested using the method Thermogravimetri and total microbial tested using Total Plate Count (TPC). Statistical analysis of water content was tested using Kruskal Wallis test and analysis of total microbes tested one-way ANOVA with a significance level of 95% continued test of Duncan Multiple Range Test (DMRT). The highest water content of a wet noodle composite flour was found at 36 hours storage time (52.2%), while the highest total microbial wet noodles composite flour was found storage time of 24 hour (7.1 log CFU/g). There was no significant effect of storage time on the water content of a wet noodle flour composites (p = 0.082). There was significant influence between the storage time of the total microbial wet noodle flour composites (p = 0.008). The acceptable storage time of wet noodle composite flour was before the 24th hour.